Acute efficacy and chronic follow-up of patients with non-thoracotomy third generation implantahle defibrillators - Brachmann, Johannes; Sterns, Laurence D.; Hilbel, Thomas; Schöls, Wolfgang; Beyer, Thorsten; Mehmanesh, Hormoz; Lange, Rüdiger; Ruf-Richter, Jutta; Kraft, Patricia; Hagl, Siegfried; Kübler, Wolfgang (Pacing and clinical electrophysiology, 1994)
Non-thoracotomy implantation of implantable cardioverter defibrillators (ICDs) has simplified the process of device inserfion, promising to decrease associated procedural coniplications while providing sudden death protection at least equal to epicardial systems. This study presents the acute and chronic results of 110 patients who underwent attempted non-thoracotomy ICD impiuntation wiih the Medtronic Transvene lead system and PCD model 7217 or 7219. Of the 110 patients attempted, 100 (91%) had the system successfully implanted without the need for an epicar-dial patch. One patient died 1 week postoperatively of septic shock related to the implantation (0.9% perioperative mortality). During folloiv-up of 16 ± 11 months, 45% of the patients had an event detected as ventricular tachycardia; 26% of these detections were felt clinically to be due to supraventricular rhythms. Of the remainder, 87% were successfully treated with the first VT therapy, and 98% were terminated by the final therapy; 66% of the patients had at least one episode of ventricular fibrillation, of which 5% were felt to be inappropriate detections; 65% of the appropriate episodes were successfully treated with the first VF therapy, and all were converted by the final therapy. Total mortality at 6, 12, and 24 months was 3%, 11%, and 19% respectively. Only one patient had sudden cardiac death, occurring at 13 months postimplant. Overall, the non-thoracotomy lead system for this ICD displayed infrequent implant complications and proved to be reliable ai terminating arrhythmias and maintaining a low rate of sudden cardiac death in this high risk popuiation.